2021
DOI: 10.1128/mmbr.00177-20
|View full text |Cite
|
Sign up to set email alerts
|

More than a Pore: Nonlytic Antimicrobial Functions of Complement and Bacterial Strategies for Evasion

Abstract: SUMMARY The complement system is an evolutionarily ancient defense mechanism against foreign substances. Consisting of three proteolytic activation pathways, complement converges on a common effector cascade terminating in the formation of a lytic pore on the target surface. The classical and lectin pathways are initiated by pattern recognition molecules binding to specific ligands, while the alternative pathway is constitutively active at low levels in circulation. Complement-mediated killing is essential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 229 publications
0
15
0
Order By: Relevance
“…Upon activation of C1, proteolytic cleavage of downstream complement components leads to a self-amplifying cascade, resulting in opsonization and phagocytosis of the target cell, modulation of adaptive immunity, neutrophil synergy, and bactericidal activity through formation of the terminal complement complex (TCC), also known as the membrane attack complex (MAC) (27). To avoid destruction of healthy self-cells, host regulators bind complement components, preventing their activation in circulation, such as C1 esterase inhibitor (C1-INH), or on the surface of cells, such as Factor H (FH) (27,28). A number of bacterial complement inhibitors have been characterized, from inhibitors of complement activation in Gram-positive pathogens, to inhibitors of the MAC in susceptible Gram-negative pathogens, as well as factors that reduce opsonization and phagocytosis by host immune cells (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation of C1, proteolytic cleavage of downstream complement components leads to a self-amplifying cascade, resulting in opsonization and phagocytosis of the target cell, modulation of adaptive immunity, neutrophil synergy, and bactericidal activity through formation of the terminal complement complex (TCC), also known as the membrane attack complex (MAC) (27). To avoid destruction of healthy self-cells, host regulators bind complement components, preventing their activation in circulation, such as C1 esterase inhibitor (C1-INH), or on the surface of cells, such as Factor H (FH) (27,28). A number of bacterial complement inhibitors have been characterized, from inhibitors of complement activation in Gram-positive pathogens, to inhibitors of the MAC in susceptible Gram-negative pathogens, as well as factors that reduce opsonization and phagocytosis by host immune cells (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in acute pyelonephritis have found that, paradoxically, Tlr4 -/- , Il1b -/- , or C3 -/- mice or mice receiving anti-inflammatory mediator cyclic AMP had less severe acute kidney infection and inflammation, suggesting that innate immune responses driven by TLR4 signaling, pro-inflammatory cytokine IL-1β, or complement effector molecules are harmful, rather than beneficial, for the host ( Springall et al., 2001 ; Yadav et al., 2010 ; Wei et al., 2015 ). With regard to the role of C5aR1 in UTI, it is worth noting a number of observations from our own and others’ published work as well as the work presented in this manuscript: i) most human UPEC strains are resistant to complement-mediated killing ( Li et al., 2009 ; Bjanes and Nizet, 2021 ), but on the other hand, excessive C5a can be generated by persistent activation of complement during infection and detected in the urine of infected mice ( Li et al., 2017 ); ii) C5aR1 is expressed in uroepithelial cells including renal tubular epithelial cells and transitional epithelium of the ureter and urinary bladder ( Zahedi et al., 2000 ), in addition to the migrated leukocytes; and iii) C5aR1 and TLR4 cross talk upon pathogen invasion has synergistic effects on proinflammatory cytokine production ( Zhang et al., 2007 ). Therefore, although C5a/C5aR1 interaction-mediated inflammatory response is generally required for fight infection, in UTI, the cross talk between C5aR1 and TLR4-mediated excessive inflammatory responses, together with the lack of complement-mediated direct killing, will lead to overactivation of immune response which is harmful rather than beneficial.…”
Section: Discussionmentioning
confidence: 85%
“…Uroepithelial cells are usually the first to respond to microbial challenge and then orchestrate the subsequent host response by release of cytokines, other mediators of inflammation, and complement proteins and stimulate the influx of neutrophils ( Spencer et al., 2014 ; Jones-Freeman et al., 2021 ). However, most human UPEC strains are resistant to complement-mediated killing ( Li et al., 2009 ; Bjanes and Nizet, 2021 ), and several lines of study have suggested that these bacteria mediate excessive inflammatory responses that cause uroepithelial destruction ( Wullt et al., 2003 ; Ambite et al., 2021 ; Paludan et al., 2021 ), impair innate immune cell function, and lead to chronic and recurrent UTI ( Hannan et al., 2010 ; Choudhry et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens have acquired sophisticated virulence factors and sensors that allow them to overcome both the colonization resistance exerted by the microbiome, and the innate and nutritional immunity of the host. Mechanistically, these proteins enable evasion and neutralization of host defenses [4,7,8]; moreover, pathogens can sense metabolites produced by the microbiota to finetune virulence gene [9,10]. Accordingly, pathogen-host interactions are multifaceted, requiring multidisciplinary approaches to study mechanisms of infection and, most importantly, to discover novel antibacterial targets.…”
Section: The Landscape Of Intestinal Infectionsmentioning
confidence: 99%